2020
DOI: 10.35848/1347-4065/ab82a6
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing of the thermal conductivity of Si nanopillar/SiGe composite films investigated by using a piezoelectric photothermal spectroscopy

Abstract: To investigate the decrease of thermal conductivity ( ) of nanoscale Si materials, we conducted the piezoelectric photothermal (PPT) method for the highly periodic Si nanopillar arrays embedded in Si0.7Ge0.3. The PPT is an electrode free method that can measure a heat propagation in the parallel to the nanopillars direction. A distinctive dip was observed in the frequency-dependent PPT signal intensity. By focusing the dip frequency, was estimated from the comparison with the model analysis based on the one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…NWs have been shown to have some improved thermal properties [72]. Li et al showed Si NWs had lower thermal conductivity compared to bulk [73], which is a useful property for making more efficient power generators that use thermoelectric materials [74].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…NWs have been shown to have some improved thermal properties [72]. Li et al showed Si NWs had lower thermal conductivity compared to bulk [73], which is a useful property for making more efficient power generators that use thermoelectric materials [74].…”
Section: Physical Propertiesmentioning
confidence: 99%
“…3, an approach to the dynamic surface tension that involved observing the high-frequency surface tension wave was introduced. As the spatial scale of the liquid process becomes smaller, especially in recent industrial fluid processes, [53][54][55][56][57][58][59] such as inkjet technologies and microfluidics, the role of the surface properties becomes more important. The contribution of the inertia energy or energy dissipation caused by viscosity is proportional to the third power of the spatial size, while the surface energy increases linearly with the square of the size.…”
Section: Measurement Of Dynamic Properties Of Liquids By High-frequen...mentioning
confidence: 99%
“…[7][8][9] Research on QCM sensors has been undertaken for a long time, however, in recent years, research on useful devices focusing on piezoelectric materials other than the quartz crystal has also been actively undertaken. [10][11][12][13][14][15][16][17][18] The QCM sensor is based on a mass detection sensor that detects the mass loading caused by binding between the target substance and the sensitive film formed on the surface of the thin quartz oscillator, which vibrates in the thickness-shear resonance, as a resonance frequency change. Therefore, it is a useful sensor, which can be applied to various applications by appropriately choosing the sensitive film.…”
Section: Introductionmentioning
confidence: 99%